2012
DOI: 10.1350/pojo.2012.85.1.571
|View full text |Cite
|
Sign up to set email alerts
|

Graffiti Offenders' Patterns of Desistance from, and Persistence in, Crime: New Insights into Reducing Recidivist Offending

Abstract: While graffiti is a gateway crime towards more serious criminal offending, little is known about graffitists' patterns of desistance from, and persistence in, crime. This paper addresses this knowledge shortfall through an examination of the Western Australian Police Information Management System (IMS) database for three age-groups (i.e. preteens, adolescents, adults) and three categories of graffiti offenders (Early Desisters, Limited Persisters, Chronic Persisters). Descriptive and chi-squared statistics rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
1
1
Order By: Relevance
“…These non-significant longitudinal findings challenge conclusions drawn from previous research examining police records (Shannon 2003;Taylor and Khan 2012;. By using a student population and controlling for key confounders, the current analyses showed that apart from alcohol use, graffiti involvement per se did not increase adolescents' future illegal activity.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…These non-significant longitudinal findings challenge conclusions drawn from previous research examining police records (Shannon 2003;Taylor and Khan 2012;. By using a student population and controlling for key confounders, the current analyses showed that apart from alcohol use, graffiti involvement per se did not increase adolescents' future illegal activity.…”
Section: Discussioncontrasting
confidence: 78%
“…Although the majority of graffiti writers tend to be male, females are also involved, particularly in tagging, which has a more balanced gender distribution (MacDonald 2001;Swedish Crime Prevention Council 2003, 2013. Graffiti initiation typically occurs around 13 to 14 years of age before peaking at around 15 years of age (Hales et al 2009;Smart et al 2004;Taylor and Khan 2012), despite some writers continuing this behavior in adulthood (Taylor, Marais, and Cottman 2012).…”
mentioning
confidence: 99%